Study of Component Composition and Antimicrobial Activity of the Ophthalmic Emulsion Based on the Safflower Flowers (Carthamus tinctorius L.) - Abuova, Zhanar; Turgumbayeva, Aknur; Jumagaziyeva, Ardak; Rakhimov, Kairolla; Jussupkaliyeva, Aigul (International Journal of Microbiology, 2022)
The use of medicinal plants has increased significantly in recent years. More than 80% of the world’s population uses medicinal plants to treat themselves. Many antibacterial and anti-inflammatory synthetic drugs are available in medical practice. However, recent tendency of increasing capability of resistance of bacteria to usage of antibacterial drugs of different groups is taking place. Considering the wide range of pharmacological and antimicrobial activity of safflower flower extracts and available vitamins in their composition, it was decided to create a preparation based on the CO2 extract of safflower (Carthamus tinctorius L.) in the form of an ophthalmic emulsion. The aim of this research is to study the composition and antimicrobial activity of the extract and ophthalmic emulsion drops against test strains of microorganisms. The subject of this study is the ophthalmic emulsions from flowers of Kazakhstan species of “Akmai” safflower, collected in the flowering stage in southern Kazakhstan in August 2021. The component composition was determined using gas chromatography with the Agilent 7890A/5975C mass spectrometry technique. A study of the antimicrobial activity of the ophthalmic emulsion drop extracts was performed with two strains of Gram-positive bacteria, one strain of Gram-negative bacteria, and one culture of fungi. The following biologically active substances were determined from the GC-MS results: tridecane 94%, tricosane 93%, hexacosane 93%, dodecanoic acid 92%, pentacosane 91%, and linoleic acid 63.7%. The investigated emulsion-type eye drop shows bactericidal activity against S. aureus ATCC 6538-P, where the zone of growth suppression under the ophthalmic emulsion action corresponded to 9.0 ± 0.0 mm. The tested ophthalmic emulsion drops show the presumed biological activity against conditionally pathogenic bacteria. The results of chromatographic analysis and antimicrobial activity of the tested samples indicate the prospects for their further study for use as anti-infectious (anti-inflammatory) agents in medicine.